2018
DOI: 10.3390/ijms19061819
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surfactant Type and Sonication Energy on the Electrical Conductivity Properties of Nanocellulose-CNT Nanocomposite Films

Abstract: We present a detailed study on the influence of sonication energy and surfactant type on the electrical conductivity of nanocellulose-carbon nanotube (NFC-CNT) nanocomposite films. The study was made using a minimum amount of processing steps, chemicals and materials, to optimize the conductivity properties of free-standing flexible nanocomposite films. In general, the NFC-CNT film preparation process is sensitive concerning the dispersing phase of CNTs into a solution with NFC. In our study, we used sonicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 58 publications
1
26
0
Order By: Relevance
“…The results from CV demonstrate that CTAB was able to provide conductive properties to NCC in order to accelerate the electron transfer on the electrode surface. As previously reported, the introduction of the CTAB surfactant has increased the dispersion of cellulose nanocrystals (CNCs) and the dispersive effect of nanoparticles increases the conductive probability [27,37]. The results also show that the electroactive surface area of SPCE/MPA-Fe 3 O 4 /NCC/CTAB was increased by approximately 54.5% compared to the bare SPCE.…”
Section: Electrochemical Characterizationsupporting
confidence: 79%
“…The results from CV demonstrate that CTAB was able to provide conductive properties to NCC in order to accelerate the electron transfer on the electrode surface. As previously reported, the introduction of the CTAB surfactant has increased the dispersion of cellulose nanocrystals (CNCs) and the dispersive effect of nanoparticles increases the conductive probability [27,37]. The results also show that the electroactive surface area of SPCE/MPA-Fe 3 O 4 /NCC/CTAB was increased by approximately 54.5% compared to the bare SPCE.…”
Section: Electrochemical Characterizationsupporting
confidence: 79%
“…Other ways include the functionalization of CNTs with self-assembling amphiphilic glycosylated proteins [142] or the use of oil-in-water Pickering emulsions of cellulose nanoparticles [143]. From the aqueous dispersions, 2D and 3D nanocellulose/CNT composites can be formed, e.g., by vacuum filtration, centrifugal cast molding, foam forming, casting and printing [39,45,50,141]. Pickering emulsions of cellulose nanocrystals and SWCNTs or MWCNTs were used for fabricating aerogels and foams by freeze-drying [143].…”
Section: Preparation and Industrial Application Of Nanocellulose/cnt mentioning
confidence: 99%
“…Similarly as in nanocellulose/graphene composites, CNTs can be added to cultures of bacteria producing nanocellulose, and incorporated into the bacterial nanocellulose during its growth [53,57]. Composite nanocellulose/SWCNT films can be transparent or semitransparent [39,45,141], and can transmit radiant energy [144].…”
Section: Preparation and Industrial Application Of Nanocellulose/cnt mentioning
confidence: 99%
“…The true conductivity potential of CNTs can be uncovered when the dispersing step to a liquid medium is performed properly to form a percolation network. Recent studies have revealed that the process of dispersing CNTs in a water-based system can be optimised so that the outcome functionality increases exponentially [14,15]. It is reported in those articles that, when using sonication as a dispersing process, the applied sonication energy to the dispersion and a properly selected surfactant play a key role when optimizing conductivity properties and dispersion quality.…”
Section: Introductionmentioning
confidence: 99%